Roots of Resistance: Deep Ecology and Environmental Justice in Song of the Trees (International Journal of Scientific Research in Science and Technology, 2024)
In Song of the Trees, Mildred D. Taylor tells the story of the Logan family, who fight to save their trees from a timber company that wants to cut them down. This paper looks at the story through "deep ecology," a philosophy that values nature not only for human use but for its own sake. By treating the trees as living beings with worth, this paper asks: How do the trees in the story mean more than just resources? What does the family’s fight to protect them show about the bond between nature and community? This study also explores how Taylor’s portrayal of the trees relates to environmental justice, especially the idea that harming nature is often tied to the oppression of marginalized groups. By looking at the Logan family’s resistance through this lens, the paper argues that their fight is not just about saving trees but also about defending their cultural identity and way of life.